RETRACTED: Microsurgical dissection methods for embryonic cloning of monozygotic twins - Babenkov Vladimir; Chimidova Nadezhda; Ubushieva Altana; Manzhiev Vasily (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001